A helicase assay based on the displacement of fluorescent, nucleic acid-binding ligands. - Eggleston, A K (1996)
We have developed a new helicase assay that overcomes many limitations of other assays used to measure this activity. This continuous, kinetic assay is based on the displacement of fluorescent dyes from dsDNA upon DNA unwinding. These ligands exhibit significant fluorescence enhancement when bound to duplex nucleic acids and serve as the reporter molecules of DNA unwinding. We evaluated the potential of several dyes [acridine orange, ethidium bromide, ethidium homodimer, bis-benzimide (DAPI), Hoechst 33258 and thiazole orange] to function as suitable reporter molecules and demonstrate that the latter three dyes can be used to monitor the helicase activity of Escherichia coli RecBCD enzyme. Both the binding stoichiometry of RecBCD enzyme for the ends of duplex DNA and the apparent rate of unwinding are not significantly perturbed by two of these dyes. The effects of temperature and salt concentration on the rate of unwinding were also examined. We propose that this dye displacement assay can be readily adapted for use with other DNA helicases, with RNA helicases, and with other enzymes that act on nucleic acids.